The diversity, population, ecology and conservation status of waterbirds in the wetland of Bangpu Nature Education Center, Thailand - Chanate Wanna; DONLA WASAN; YOKCHOM PISARUT; SOI-AMPORNKUL RUNGTIP (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Chanate W, Wasan D, Pisarut Y, Rungtip S. 2020. The diversity, population, ecology, and conservation status of waterbirds in the wetland of Bangpu Nature Education Center, Thailand. Biodiversitas 21: 3910-3918. Wetlands are a crucial habitat for waterbirds as they provide feeding and breeding sites and increase survival rates during the non-breeding season. This study aimed to update the status of waterbirds in Bangpu Nature Education Center, Samut Prakarn Province, Thailand by evaluating the species diversity and abundance. The ground count survey was conducted at 3 habitats: mangrove forest, mudflat, and bungalow accommodation from March to October 2017. A total of 34 waterbird species classified under 5 orders, 8 families, and 22 genera were observed. The majority of waterbird species (23 species) were found in the mudflat area with the least number (12 species) observed in the bungalow accommodation location. The Shannon-Weiner diversity index (H’) showed that the mudflat area had significantly greater diversity compared with the other sites. The mudflat area also had the greatest species richness (D) (2.89) and species evenness index (E) (0.38), respectively. The Sorensen similarity index (CS) indicated that the greatest similarity in species (66.67%) was found between the mangrove and bungalow areas. A total of 6 residents, 20 migratory species, and 8 species with both resident and migratory populations were found with 4 species classified as abundant, 3 as common, 15 as moderately common, and 12 as uncommon species identified. In addition, the conservation status of waterbirds is becoming increasingly important with 5 near-threatened species (NT) already identified according to IUCN, 2016 and Red Data of Thailand, 2007, consisting of Heteroscelus brevipes, Limosa limosa, Numenius arquata, Mycteria leucocephala and Vanellus cinereus. It is recommended that monitoring the conservation status of the Bangpu wetlands should be continued to maintain waterbird diversity.